Immunogenicity of recombinant fragment of orthopoxvirus p35 protein in mice - Ya. A. Khlusevich; A. L. Matveev; E. P. Goncharova; I. K. Baykov; N. V. Tikunova (Вавиловский журнал генетики и селекции)
Despite the elimination of smallpox, orthopoxviruses continue to be a source of biological danger for humans, as cowpox and monkey pox viruses circulate in nature and the last virus can cause both sporadic cases of human diseases and outbreaks of smallpox-like infection. In addition, periodic vaccination is necessary for representatives of some professions (scientists studying pathogenic orthopoxviruses, medical personnel, etc.). Vaccination against smallpox virus with live vaccinia virus, which was widely used during the elimination of smallpox, induces the formation of long-term immunity in vaccinated people. However, providing a high level of protection, the vaccination is often accompanied by serious post-vaccination complications, the probability of which is particularly great for individuals with compromised immunity. In this regard, the development of preparations for the prevention and treatment of infections caused by orthopoxviruses remains important today. The aim of this study was to assess the immunogenicity in the mouse model of recombinant protein р35Δ12, designed previously on the base of the cowpox virus protein p35. It was previously shown that the protein р35Δ12 was recognized by fully human neutralizing anti-orthopoxviral antibody with high affinity. In this work, recombinant protein р35Δ12 produced in E. coli cells XL1-blue and purified by chromatography was used for two-time immunization of mice. Two weeks after the second immunization, blood samples were taken from mice and serum antibodies were analyzed. It was shown by ELISA and Western-blot analysis that immunized mice sera contained IgG antibodies specific to recombinant protein р35Δ12. Confocal microscopy showed that antibodies induced by the р35Δ12 protein were able to recognize Vero E6 cells infected with the LIVP-GFP vaccinia virus. In addition, the antibodies in the serum of immunized mice were able to neutralize the infectivity of the vaccinia virus LIVP-GFP in the plaque reduction neutralization test in vitro. These experiments have demonstrated promising properties of the р35Δ12 protein if it were used as a component of vaccine for prophylaxis of orthopoxvirus infections.